Capacity investment under demand uncertainty: An empirical study of the US cement industry, 1994-2006 - Jean-Pierre Ponssard; Catherine Thomas (Center for Economic Studies and ifo Institute (CESifo), 2010)
Uncertainty about the level of demand is thought to influence irreversible capacity decisions. This paper examines some implications of the theory literature on this topic in an empirical study of the US cement industry between 1994 and 2006. Firms in this sector have the ability to deliver cement either from domestic plants or from imports. Since cement is costly to transport via land, the difference in marginal cost between local production and imports varies across local markets. The marginal cost of imports is lower in areas with access to a sea port, decreasing the relative value of investing in local capacity sufficient to supply positive local demand shocks. In the presence of uncertain demand, firms may choose to serve these markets via both domestic production and imports. Consistent with the theory, we find a negative relationship between the average level of excess capacity and demand volatility only for coastal areas. An increase in demand volatility is associated with an increase in excess capacity only in landlocked areas. More generally, the paper shows that the cost of imports relative to the cost of domestic production affects the relationship between uncertainty and domestic capacity decisions. The results suggest that a unilateral climate policy in the US may induce a partial international relocation of capacity in carbon intensive industries, such as cement, by increasing the relative cost of domestic production.
Keywords: D24; D81; F18; L61; 330; capacity investment; demand uncertainty; imports; cement; Zementindustrie; Produktionskapazität; Investition; Entscheidung bei Unsicherheit; Zement; Nachfrage; Import; Transportkosten; Klimaschutz; Wirkungsanalyse; USA